Attributes of evidence-based occupational therapists in stroke rehabilitation. (December 2018) - Hallé, Marie-Christine; Mylopoulos, Maria; Rochette, Annie; Vachon, Brigitte; Menon, Anita; McCluskey, Annie; Amari, Fatima; Thomas, Aliki
Background: A better understanding of the features characterizing expert evidence-based occupational therapists in stroke rehabilitation is needed to inform the design of educational and knowledge translation interventions aimed at addressing research–practice gaps. Purpose: The study aimed to identify the attributes of evidence-based occupational therapy stroke rehabilitation experts from the perspective of their peers. Method: Forty-six occupational therapy clinicians and managers completed an online questionnaire asking them to nominate "outstanding" and "expert evidence-based" occupational therapists in stroke rehabilitation and to explain their choices. A thematic analysis of respondents' statements was conducted. Findings: Both outstanding and expert evidence-based occupational therapists were perceived to be motivated self-learners; to have extensive knowledge, skills, and experience; to act as scholarly practitioners; to achieve superior client outcomes; and to work in specialized settings. Implications: The development of future strategies supporting occupational therapy students and clinicians to become lifelong learners should take into account key attributes of expertise, such as motivation for continuous learning and professional development.